The effects of tamoxifen on radiation-induced pulmonary fibrosis in Wistar albino rats: Results of an experimental study - Bese, Nuran Senel; Umay, Cenk; Yildirim, Sukru; Ilvan, Sennur; Dirican, Ahmet; Salar, Seda; Altug, Tuncay; Ober, Ahmet (BREAST, 2006)
This study was performed to evaluate the effects of tamoxifen on pulmonary fibrosis, given concurrently with or after irradiation in Wistar albino rats. Twenty-one female Wistar albino rats were randomized into three groups. The first group (Group A) had tamoxifen, which was started after the completion of irradiation. The second group (Group B) had tamoxifen concomitant with irradiation. The third group (Group C) had only thoracic irradiation and did not receive tamoxifen. Whole lungs were irradiated to a total dose of 30 Gy in ten fractions with Co60. Tamoxifen was continued until the animals were sacrificed 16 weeks after the start of irradiation. As an end point the percentage of lung with fibrosis for each rat was quantified with image analysis of histological sections of the lung. Groups were compared using the one-way ANOVA method and Bonferroni post hoc test. The mean percentage values of fibrosis were 10.03 for Group A, 36.81 for Group B, and 3.87 for group C (P < 0.001). When the percentages of fibrosis were compared for each group, the difference was statistically significant between Group A and Group B (P < 0.001) and between Group B and Group C (P < 0.001). Concomitant use of tamoxifen appears to increase radiation-induced pulmonary fibrosis and it seems more convenient to delay tamoxifen until the completion of irradiation. © 2005 Elsevier Ltd. All rights reserved.
Created from Fastlane, Scopus look-up
Keywords: Irradiation; Pulmonary fibrosis; Rats; Tamoxifen